2014
DOI: 10.1007/s12155-014-9512-y
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pretreatment with White Rot Fungi and Modification of Primary and Secondary Cell Walls Improves Saccharification

Abstract: Plant cell walls have protective and structural functions conferring resistance to degradation. The lignin and hemicellulose network surrounding the cellulose microfibrils is insoluble unless subjected to harsh treatments. As lignin, pectin and xylan are effective barriers to cellulose extraction and hydrolysis, reducing their presence in cell walls improves saccharification. Microorganisms that can depolymerise lignin are of extreme interest to the biofuel industry. White rot fungi can be effective in pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The highest colour removal of 98.46% was obtained at pH 6 but decreased to 95.69% as the pH increases to 7. Basically, the colour pigments in POME such as the phenolic, pectin and lignin, dissociate to generate negatively charged radicals in the acidic solution [ 59 ]. On the other hand, the acidic media favours the oxidation of the pretreated CSAC to acquire positive charges on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The highest colour removal of 98.46% was obtained at pH 6 but decreased to 95.69% as the pH increases to 7. Basically, the colour pigments in POME such as the phenolic, pectin and lignin, dissociate to generate negatively charged radicals in the acidic solution [ 59 ]. On the other hand, the acidic media favours the oxidation of the pretreated CSAC to acquire positive charges on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…These materials contain a large amount of cellulose and hemicellulose. Edible mushrooms rely on extracellular enzymes such as cellulase and xylanase to degrade cellulose and hemicellulose to produce monosaccharides that enter the central carbon metabolism (EMP, PPP, and TCA cycle) to provide energy and materials for mycelial growth and development [34,35]. In a recent study, QS autoinducers were found to increase the transcript level of lignin-degrading enzyme genes in H. marmoreus [20].…”
Section: Discussionmentioning
confidence: 99%